PENGARUH COMMUNICATION DAN OPPORTUNISTIC BEHAVIOR CONTROL TERHADAP TRUST PELANGGAN SHOPEE - Gian Luthfi Yusuf Matduri; Islamuddin Islamuddin (Yayasan Insani Mandiri Santani, 2022)
This study aims to determine the effect of communication and opportunistic behavior control towards trust on Shopee’s customers in the Study on students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu. The population in this study are from students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu which amounted to 1100 people. The sample in this study were 91 respondents. Methods Data collection is done by providing a list of questions or questionnaires to respondents who are students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu, where the questionnaire is distributed through the WhatssApp application. This research uses data analysis tool that is with the validity and reliability test, then this research uses multiple linear regression analysis method. While testing the hypothesis tested with the test hypothesis F (Goodness of Fit) and Test t-Statistics (Partial). The result of the research shows that 1) Communication has positive and significant effect on trust in students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu, 2) Opportunistic behavior control has positive and significant effect on trust in students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu. Keywords : Communication, Opportunistic Behavior Control, Trust